KADAR GAS HIDROGEN SULFIDA (H2S) DAN KELUHAN SUBYEKTIF PEMULUNG TPA BENOWO SURABAYA TAHUN 2016 - Suci Chintia Ivana; Rachmaniyah .; Demes Nurmayanti (Poltekkes Kemenkes Surabaya, 2017)
ABSTRACTH2S gas produced from the decomposition of waste with bad odor lead to subjective complaint forscavenger at Benowo, Surabaya the landfill when they are exposed too long. Preliminary survey on subjectivecomplaint showed that there were three people experienced dizziness, 4 people experience eye irritation, 2 withcoughing, and 6 people did not experience any complaint. The aim of the study was to determine the level of H2Sgas and scavengers‟ health complaints in Benowo, Surabaya landfill.This is a descriptive research with cross sectional approach. The population was 350 inhabitants with 36 ofthem were used as population. The primary data collection was carried out by observation, questionnaires andmeasurements of air samples, while the secondary data was the map of Benowo landfill. Data processing techniqueused editing, tabulation, textular.The results of the study on H2S gas examination in Benowo landfill showed that the average exceeds thethreshold value of 0.20 ppm. The result of measurements of the highest temperatures was during the day of 35,0⁰Cwith 54% humidity and wind speed of 1.34 m/s. 14 scavengers suffered minor complaint, 16 suffered minorcomplaint, and 6 suffered heavy complaint. High levels of H2S gas can be influenced by the accumulation of garbageand climate. High levels of H2S gas can also cause the occurrence of subjective complaints of scavengers.The conclusion shows that on the low level of H2S, the scavengers suffered mild and moderate complaints,at high levels of H2S, the scavengers suffered heavy complaints. The relevant institutions should monitor air qualityboth physically and chemically. The scavengers should conduct periodic medical examinations. The next research canuse other air pollutant parameters.Keywords: H2S gas Level, subjective complaints, scavengers